1981
DOI: 10.1071/ch9811433
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical reductions of arenediazonium ions in aqueous solution. V. Pulse-radiolytic determination of rate constants for some para-substitutedbenzenediazonium ions

Abstract: Some rate constants for the reduction of para-substituted benzenediazonium ions by the radicals eaq-, ·CH2OH, (CH3)2·COH and some semiquinone radical anions have been measured. The substituent group has no effect on the rates with eaq-, but as the reduction potential of the reducing radical becomes more positive, the substituent effect increases, electron-withdrawing groups enhancing the rates. No free halide is formed on reduction of p-BrC6H4N2+ or p-IC6H4N2+ by eaq- or ·CH2OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This should make it possible to investigate the kinetic features of reactions involving Ar • and ArN 2 + . The focus in this paper thus clearly differs from that in previous pulse radiolysis studies of diazonium salts, , where the purpose has been either to study second-order radical−radical processes by employing high radiation doses 22 or to initiate chain processes involving alcohols and radicals derived thereof . In a subsequent paper, we will present the results pertaining to the other strong reductant generated in pulse radiolysis, the hydrogen atom…”
Section: Introductionmentioning
confidence: 98%
“…This should make it possible to investigate the kinetic features of reactions involving Ar • and ArN 2 + . The focus in this paper thus clearly differs from that in previous pulse radiolysis studies of diazonium salts, , where the purpose has been either to study second-order radical−radical processes by employing high radiation doses 22 or to initiate chain processes involving alcohols and radicals derived thereof . In a subsequent paper, we will present the results pertaining to the other strong reductant generated in pulse radiolysis, the hydrogen atom…”
Section: Introductionmentioning
confidence: 98%
“…Some absolute rate constants for the one-electron reduction of the diazonium ions were measured using the technique of pulse radiolysis. 6 Much more recently it has been reported that radical-ion chain reactions can occur on one-electron reduction or oxidation of diazoalkanes in aprotic solvents. From chemical ' and electrochemical * studies of 9-diazofluorene (FIN,), reactions (1) and (2) were postulated to account for high yields of difluoren-FIN,-' + FIN,----, FlNNFl-' + N,…”
mentioning
confidence: 99%
“…Because HO • is formed in pulse radiolysis along with e aqand H • , the characteristics of the OH adducts of the diazonium salts are also described briefly herein. The focus in this paper thus clearly differs from that in previous pulse radiolysis studies of diazonium salts, 18,19 where the purpose either has been to investigate second-order radical-radical processes by employing high radiation doses 18 or to initiate chain processes involving alcohols and radicals derived thereof. 19 The radiation of water using high-energy electrons leads to the formation of the species shown in eq 7, where the radiation chemical yields of the three principal radicals are G(e aq -) ≈ G(HO • ) ≈ 2.8 × 10 -7 mol J -1 and G(H • ) ≈ 0.6 × 10 -7 mol J -1 : 17 The solvated electron can be converted to H • in a deoxygenated solution at low pH (eq 8, k 8 ) 2.3 × 10 10 M -1 s -1 ) or to HO • in a N 2 O saturated solution (eq 9, k 9 ) 9.1 × 10 9 M -1 s -1 ): 20 Under such conditions, the radiation yields become G(H • ) ≈ 3.4 × 10 -7 mol J -1 and G(HO • ) ≈ 5.6 × 10 -7 mol J -1 , respectively, or even slightly larger because the above fast reactions may take place in the spurs before homogeneous conditions are attained.…”
Section: Introductionmentioning
confidence: 97%
“…The focus in this paper thus clearly differs from that in previous pulse radiolysis studies of diazonium salts, 18,19 where the purpose either has been to investigate second-order radical-radical processes by employing high radiation doses 18 or to initiate chain processes involving alcohols and radicals derived thereof. 19 The radiation of water using high-energy electrons leads to the formation of the species shown in eq 7, where the radiation chemical yields of the three principal radicals are G(e aq -) ≈ G(HO • ) ≈ 2.8 × 10 -7 mol J -1 and G(H • ) ≈ 0.6 × 10 -7 mol J -1 : 17 The solvated electron can be converted to H • in a deoxygenated solution at low pH (eq 8, k 8 ) 2.3 × 10 10 M -1 s -1 ) or to HO • in a N 2 O saturated solution (eq 9, k 9 ) 9.1 × 10 9 M -1 s -1 ): 20 Under such conditions, the radiation yields become G(H • ) ≈ 3.4 × 10 -7 mol J -1 and G(HO • ) ≈ 5.6 × 10 -7 mol J -1 , respectively, or even slightly larger because the above fast reactions may take place in the spurs before homogeneous conditions are attained. The procedure for scavenging HO • , H • , and X-C 6 H 4 • usually involves tert-butanol as depicted in eqs 10-12 (k 10 ) 6.0 × 10 8 M -1 s -1 , k 11 ) 1.7 × 10 5 M -1 s -1 , and k 12 ) 6.6 × 10 5 M -1 s -1 for X ) H): 20,21 In most experiments of the present study, we had to accept the presence of HO • because its scavenging would be accompanied by the scavenging of X-C 6 H 4 • produced along the reaction pathway.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation